2012
DOI: 10.1111/myc.12030
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and lactose as cryoprotectants for fungal strains immobilised in sodium alginate: an emphasis on the conservation of the zygomycetes Rhizopus and Mucor

Abstract: This research aimed at investigating the cryoprotectant action of glucose and lactose on strains of Malassezia spp. and zygomycetes immobilised in sodium alginate. Twelve strains of Malassezia spp. (nine M. furfur, two M. globosa and one M. sympodialis) and 12 zygomycetes (five Rhizopus oryzae and seven Mucor hiemales) were immobilised in sodium alginate, within plastic beads, maintained in appropriate media containing glucose and lactose at concentrations of 9% and 23% and preserved at temperatures of -20 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…3,7,17,18 Therefore, cryopreservation is the currently preferred technique in many culture collections because it decreases cell metabolic activity, allowing the isolates to remain stable for extended periods of time, in addition to preventing colony contamination. 9,12 On the other hand, the freezing process can irreversibly damage fungal cells, and hence, different cryoprotectants have been used to reduce cell damage. 9 In this study, the use of glycerol as a penetrating cryoprotectant associated with the nonpenetrating cryoprotectants sucrose or lactose was shown to be a valid alternative for the cryopreservation of the S. schenckii species complex, resulting in 100% recovery, even after 9 months of storage, at both -20°to -80°C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,7,17,18 Therefore, cryopreservation is the currently preferred technique in many culture collections because it decreases cell metabolic activity, allowing the isolates to remain stable for extended periods of time, in addition to preventing colony contamination. 9,12 On the other hand, the freezing process can irreversibly damage fungal cells, and hence, different cryoprotectants have been used to reduce cell damage. 9 In this study, the use of glycerol as a penetrating cryoprotectant associated with the nonpenetrating cryoprotectants sucrose or lactose was shown to be a valid alternative for the cryopreservation of the S. schenckii species complex, resulting in 100% recovery, even after 9 months of storage, at both -20°to -80°C.…”
Section: Discussionmentioning
confidence: 99%
“…Cryotubes containing saline were stored at 4°C, while those containing the cryoprotectants GL and GS were kept at -20°C and -80°C, for periods of 3, 6, and 9 months. 12,13 Viability of stored strains and conidium count At the end of each period, the strains were removed from storage and subcultured on potato dextrose agar medium (Difco, USA). Viability was defined as the ability to grow on potato dextrose agar, after storage, under any of the tested conditions.…”
Section: Storagementioning
confidence: 99%
See 1 more Smart Citation
“…The BGLs of patients of Group C are higher than 10.0 mmol/L. Among the critically ill ICU patients, the proportion of fungal infection is up to 50% primarily because blood osmotic pressure increases with high BGL, and this increase inhibits the phagocytic functions of neutrophils, reduces the ability of the body to resist infection, and causes abnormalities in the immune system, thereby promoting the spread of fungal infection and adding value to deep organizations [8]. Bueno [9] investigated the situation of fungal infection among ICU patients and reported that their BGLs should be monitored.…”
Section: Discussionmentioning
confidence: 99%